A systematic mapping study on customer loyalty and brand management - Andrea Moretta Tartaglione; Ylenia Cavacece; Giuseppe Russo; Giuseppe Granata (Administrative Sciences, 2019)
Customer loyalty is a topic of great interest for marketing scholars due to its importance in gaining sustainable competitive advantages and financial outcomes. Literature is prolific of works regarding customer loyalty and brand management. In order to improve the quantity and quality of research publications, research themes mapping of published studies is required. The aim of this paper is to provide scholars with a systematization and mapping of the contributions on this topic to develop an effective research road map for future research. A bibliometric analysis and a mapping study have been conducted on 337 publications on customer loyalty and brand management from 2000 to 2018. The results present the most cited works on the topic, an evaluation map showing the most frequent and cited words and six clusters of words based on their co-occurrence. From the analysis of the clusters, the most relevant research findings, trends, and issues emerge, suggesting interesting theoretical and practical implications.
Keywords: 350; customer loyalty; brand; satisfaction; commitment; trust; engagement; bibliometric analysis; mapping study